Fault Diagnosis Algorithm and Protection of Electric Power Systems in an Alternative Distribution System - Oshin Ola Austin; Oluwasanmi Alonge; Ajayi Joseph Adeniyi (Journal La Multiapp, 2020)
In any power systems, protective devices will detect fault conditions and operate circuit breakers in order to disconnect the load from the fault current and limit loss of service due to failure. This fault may involve one or more phases and the ground, or may occur between two or more phases in a three-phase systems. In ground, fault’ or ‘earth fault, current flows into the earth. In a poly-phase system, a fault may affect each of the three phases equally which is a symmetrical fault. If only some phases are affected, the resulting ‘asymmetrical fault’ becomes more complicated to analyze due to the simplifying assumption of equal current magnitude in all the phases being no longer applicable. Therefore, the prospective short circuit current of the fault can be calculated for power systems analysis procedures. This will assist in the choice of protective devices like circuit breakers, current transformers and relays. This research work evaluated and analyzed the occurrence of faults in a distribution system. Fault currents were obtained and the maximum tripping time required for the protective devices to operate were determined. Hence, it was possible to select appropriate relay and circuit breaker for effective operation of a distribution